Development of a PMV-based thermal comfort modelling - Shazmin Aniza, Abdul Shukor; Karl Kohlhof; Zul Azhar, Zahid Jamal (International Association of Science and Technology for Development (IASTED)/ACTA Press, 2009)
Link to publisher's homepage at http://www.iasted.org/